2014
DOI: 10.1007/s10955-014-1107-7
|View full text |Cite
|
Sign up to set email alerts
|

Optimal $$N$$ N -Point Configurations on the Sphere: “Magic” Numbers and Smale’s 7th Problem

Abstract: This paper inquires into the concavity of the map N → v s (N ) from the integers N ≥ 2 into the minimal average standardized Riesz pair-energies v s (N ) of Npoint configurations on the sphere S 2 for various s ∈ R. The standardized Riesz pair-energy of a pair of points on S 2 a chordal distance r apart is V s (r) = s −1 (r −s − 1), s = 0, which becomes V 0 (r) = ln

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 88 publications
0
13
0
Order By: Relevance
“…For instance, even the absolutely energy-minimizing 5-particle arrangement on S d changes several times when s varies over the real line, apparently: ( ) For s < −2, all minimizers are either triangular or antipodal [Bjo56], independently of d. In Appendix 1 of [NBK14] it is reported that their own computer-assisted results showed that an antipodal arrangement of two point particles at the South and three at the North Pole is the optimizer for s ≤ −2.368335...; at s = −2.368335... a crossover takes place, and for −2.368335... ≤ s ≤ −2 an isosceles triangle on a great circle, with one particle in the North Pole and two particles each in the other two corners, with (numerically) optimized height, is an energy-minimizing arrangement of five point particles. This has yet to be proved rigorously.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, even the absolutely energy-minimizing 5-particle arrangement on S d changes several times when s varies over the real line, apparently: ( ) For s < −2, all minimizers are either triangular or antipodal [Bjo56], independently of d. In Appendix 1 of [NBK14] it is reported that their own computer-assisted results showed that an antipodal arrangement of two point particles at the South and three at the North Pole is the optimizer for s ≤ −2.368335...; at s = −2.368335... a crossover takes place, and for −2.368335... ≤ s ≤ −2 an isosceles triangle on a great circle, with one particle in the North Pole and two particles each in the other two corners, with (numerically) optimized height, is an energy-minimizing arrangement of five point particles. This has yet to be proved rigorously.…”
Section: Discussionmentioning
confidence: 99%
“…1 An "optimal energy configuration" is an absolute minimizer of the configurational Riesz s-energy. For background reading concerning the quest for optimal Riesz s-energy configurations of N point particles on S 2 and other manifolds, see the survey articles 2 [ErHo97], [SaKu97], [HaSa04], Appendix 1 in [NBK14], the websites [BCM] and [Wom09], and the related article [AtSu03]. 1 The discontinuous jumps of R s (r) at s = 0 cause some artificial difficulties when trying to compare optimal energies at negative, zero, and positive s values.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations